Pengaruh Media Sosial, Literasi Keuangan, E-commerce, Digital Payment, dan Orientasi Wirausaha Terhadap Kinerja UMKM di Kota Mataram - Khotmi, Herawati; Hikmah, Husnul; Fauzi, Agus Khazin; Astini, Yuli (Valid: Jurnal Ilmiah, 2024)
This study aims to test and analyze the influence of social media, financial literacy, e-commerce, digital payment, and entrepreneurial orientation on the performance of MSMEs. The population in this study were MSME actors spread across Mataram City. Where in the sampling of the study using the proportionate stratified random sampling method. To determine the minimum sample using the Slovin formula where the amount of data obtained and can be processed is 108 respondents. Data analysis using multiple linear regression. The results of the study showed that social media and digital payment have a positive and significant effect on the performance of MSMEs. This indicates that the respondents in this study have used social media as a promotional tool for their businesses and used digital payment as an alternative to non-cash payments. Meanwhile, financial literacy, e-commerce and entrepreneurial orientation do not have a significant effect on the performance of MSMEs. It can be explained that most of the MSME actors who were respondents in this study still have low financial literacy, the use of e-commerce is not optimal and the entrepreneurial orientation that is carried out is still mostly following suit so that it does not affect the performance of the MSMEs they have.